Redeveloping expertise in the transition from coach to coach education tutor - Stephens, D.; Stodter, A.; Timmis, M. (International Sport Coaching Journal, 2025)
The role of the tutor in delivering formal coach education is critical in understanding the professional preparation of sport coaches. The recruitment, development, and retention of tutors with expertise is crucial to organisational success and has personal and professional implications for career transitions in coaching. This study focuses on teaching and learning experiences during the initial tutor training of novice coach education tutors from a national sport governing body in the United Kingdom. Grenier and Kehrhahn`s Model of Expertise Redevelopment is utilised as a theoretical tool to aid understanding of the transition from coaching to tutoring. Data were collected through document analysis, observations during and after initial tutor training and subsequent live delivery of courses, and follow-up semistructured interviews with nine tutors. The themes highlighted the need to acquire specific knowledge of the content, the role of others in the development of expertise, the use of situated learning as a catalyst for redevelopment, and the eagerness to establish their future learning pathway. The findings suggest that each territory of expertise (i.e., content, constituency and environment) did not remain stable when transitioning to the new domain of coach education tutoring and implications for future tutor training are provided.